Analisis Risiko Keselamatan dan Kesehatan Kerja Menggunakan Metode Bow Tie di PT. X - Gilang Permata, Ekie; Ihsan Hamdy, Muhammad; ardi, muhammad fajri (IDENTIFIKASI, 2021)
The palm oil mill industry has many risk to occupational safety and health. There are still many work accidents that occur resulting in losses for the company. Therefore, it is necessary to do a risk analysis wit importance index that assesses risk by considering the frequency index and sevarity index. Risk assessment is carried out by experts namely mill manager, mill assistants, and foreman. Then the risk identification is done based on the cause and effect of the risk using the bow tie methode. Risk assessment indicators use risk indicators from palm oil mills. From 54 risk indicators there are 3 significant risk, namely employees exposed to hot iron (stew operation), employees inhaled / exposed to chemicals (wtp operation), noise ( engine room operation). And there are 2 high risks, namely employees exposed steam to hot steam (stew operation), employees exposed to fire bursts (boiler operation). The causes of significant and high risks are leaking pipes, opening the stew doors when high pressure, stew doors are not tightly closed, employee negligence, employees do not obey work instructions, high air pressure, lack of noise absorbent, material, there are worn, engine parts. The impact of significant and high risk are burns to the skin, material loss, shortness of breath, skin irritation, communication, disorders, damage to hearing. Control of sginificant and high risk using a complete PPE, providing evacuation tools.